Pd(0), Pd(II) electromerism triggered by Lewis base coordination to a redox-active silicon Z-type ligand - Ansmann, Nils; Kerscher, Marion; Greb, Lutz (Angewandte Chemie. International edition, 2025)
Electromerism (aka. valence tautomerism) corresponds to the switching of electronic distributions between redox-active ligands and central elements. While this phenomenon is well established for several transition metals, the Pd(0)/Pd(II) couple could not yet be involved due to the high energy of the Pd(0) state. In this study, we present Pd(0)/Pd(II) electromerism by using a redox-active bis(phosphanyl-amidophenolato)silane. Strong silicon-based Z-type interaction stabilizes the Pd(0) state with an oxidized dicationic open-shell singlet ligand while binding of a Lewis base at the Lewis acidic silicon results in the loss of Z-type interaction and the intramolecular rearrangement to the Pd(II)/reduced ligand electromer. It introduces a novel concept for spin state switching by combining ligand ambiphilicity and redox activity.